Training Evaluation Models for Farmer Training Programmes - Masta, Karan; Janjhua, Yasmin (International Journal of Economic Plants, 2020)
Training has been an effective means to attain knowledge, skill and abilities adding to human efficiency and effectiveness. Ensuring effective training means knowing whether investment of time, energy and resources are being spent effectively or not. Active play of diverse resources makes it imperative to evaluate the effectiveness of the training. The paper attempts to explain the important models of training evaluation which can be adopted by practitioners for evaluating farmer trainings. These approaches can be used as a base to assess farmer training interventions and also help to revise and design an intervention which is effective and free from impediments.